Multi-objective Optimization of the Extrusion Process. (2015) - Reggiani, Barbara; Donati, Lorenzo; Tomesani, Luca
Abstract: In the paper a multi-objective optimization of a porthole extrusion die used to manufactured a thick AA7003 round tube is presented. Eight competitive objective functions were selected aimed at increasing the seam weld quality, the die lifetime, the production rate and at restraining the die yielding and the peak process load with respect to an initial already optimized solution. Six geometric input variables were included in the optimization procedure (welding chamber and bridges height, ports width, undercut on ports, die entry angle, mandrel-bridges fillet radius) together with the ram speed. The multi-objective optimization was performed by means of modeFRONTIER® using meta-models generated over a selected set of experimental and numerical training designs.